A Remotely Controlled Transformable Soft Robot Based on Engineered Cardiac Tissue Construct. Issue 18 (25th March 2019) - Xu, Bingzhe; Han, Xiaomin; Hu, Yuwei; Luo, Yiming; Chen, Chia‐Hung; Chen, Zi; Shi, Peng
Abstract: Many living organisms undergo conspicuous or abrupt changes in body structure, which is often accompanied by a behavioral change. Inspired by the natural metamorphosis, robotic systems can be designed as reconfigurable to be multifunctional. Here, a tissue‐engineered transformable robot is developed, which can be remotely controlled to assume different mechanical structures for switching locomotive function. The soft robot is actuated by a muscular tail fin that emulates the swimming of whales and works as a cellular engine powered by the synchronized contraction of striated cardiac microtissue constructs. For a transition of locomotive behavior, the robot can be optically triggered to transform from a spread to a retracted form, which effectively changes the bending stiffness of the tail fins, thus minimizing the propulsion output from the "tail fin" and effectively switching off the engine. With the unprecedented controllability and responsiveness, the transformable robot is implemented to work as a cargo carrier for programmed delivery of chemotherapeutic agents to selectively eradicate cancer cells. It is believed that the realization of the transformable concept paves a pathway for potential development of intelligent biohybrid robotic systems. Abstract : A tissue‐engineered transformable robot is developed, which can be remotely controlled to assume different mechanical structures for switching locomotive functionality. With the unprecedented controllability and responsiveness, the transformable robot can be implemented for programmed eradication of cancer cells for instance. This design concept paves the way for the potential development of intelligent biohybrid robotic systems.